The Effect of Murabahah, Musyarakah, Mudharabah Financing on Profitability with Banksize is a Control Variabel in Islamic Comercial Bank - Dinsa Selia Putri,; Segaf, (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
This research analyzes the effect of murababahah, musyarakah and mudharabah financing on the profitability of Islamic commercial banks, considering the size of the bank as a control variable. Population of this research is Islamic commercial banks registered with the OJK, sampling method was used to select five companies that meet the criteria. The Eviews 12 analytic tool supports the quantitative methodology of this study. The research results show that murabahah financing has a negative and significant effect on profitability, as early repayments without penalties reduce total profit, despite higher margins set for longer terms. Musyarakah financing has no effect on profitability, because musyarakah financing allocates profits based on capital contribution or predetermined ratios; however, its medium to long term nature limits it is contribution to the value added growth of profitability. Meanwhile, mudharabah financing and banksize have a positive and significant effect on profitability, because mudharabah financing positively influences profitability, as higher profit sharing returns increase bank income and improve profitability. Greater bank assets expand operations and customer reach, supporting higher profitability. Based on the results of the f test, all independent variables in this study have an effect on profitability. Islamic commercial banks are expected to maintain strong financial performance in the coming years to sustain public trust, customer confidence, and stakeholder support.